A one‐step rectification of sperm cell targeting ensures the success of double fertilization. Issue 5 (11th March 2015) - Huang, Jilei; Ju, Yan; Wang, Xiangfeng; Zhang, Quan; Sodmergen,
Abstract: Successful fertilization in animals depends on competition among millions of sperm cells, whereas double fertilization in flowering plants usually involves just one pollen tube releasing two immobile sperm cells. It is largely a mystery how the plant sperm cells fuse efficiently with their female targets within an embryo sac. We show that the initial positioning of sperm cells upon discharge from the pollen tube is usually inopportune for gamete fusions and that adjustment of sperm cell targeting occurs through release and re‐adhesion of one sperm cell, while the other connected sperm cell remains in stagnation. This enables proper adhesion of each sperm cell to a female gamete and coordinates the gamete fusions. Our findings reveal inner embryo sac dynamics that ensure the reproductive success of flowering plants and suggest a requirement for sperm cell differentiation as the basis of double fertilization.